Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2022)
A dataset containing 98574 species occurrences available in GBIF matching the query: { "and" : [ "TaxonKey is Haliaeetus albicilla (Linnaeus, 1758)", "DatasetKey is Observation.org, Nature data from around the World", "Country is one of (Germany, France, Spain, Portugal, Denmark, Austria, Italy, Switzerland, Greece, Poland, Hungary, Slovenia, Sweden, Norway, Slovakia, Montenegro, Croatia, North Macedonia, Serbia, Iceland, Ireland, United Kingdom of Great Britain and Northern Ireland, Albania, Bosnia and Herzegovina, Bulgaria, Belgium, Netherlands)" ] } The dataset includes 98574 records from 1 constituent datasets: 98574 records from Observation.org, Nature data from around the World. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences